Factors that Affect Demand Creation for Health Services: Literature Review - Shafira Putri Yufa; Diansanto Prayoga (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The prosperity of the country is represented by a healthy society. The existence of a demand for public health services is greatly influenced by quality and fair health providers, so that based on the aspect of being a health provider they are able to provide health services when there is an increase in demand from the community. Objective: The aim of this literature review is to determine the variables that influence demand for health services. The findings of this literature study are expected to be a starting point for future studies and to provide insight into health service quality management in various health service providers. Method: . This article was written using a literature review, namely an international literature search carried out using databases such as ScienceDirect and Proquest. Inclusion criteria include articles that discuss community demand for health services. Result: Article search results show that there are 7 (seven) related studies. Gender, place of residence, level of education, employment before retirement, age, health financing, technology, norms, values, and accessibility are several factors that influence people's demand for health services. This study reveals these factors. Additionally, this study emphasizes accessibility factors, which significantly influence the demand and allocation of health promotion services. This is because health services are considered emergency and require improvement in the available health centers. Conclusion: Based on the results of the review, it can be concluded that there are several factors that influence the creation of demand or demand for health services at the Community Health Center. Factors such as gender, place of residence, education level, employment before retirement, age, health financing, heat waves, technology, values and norms, and accessibility significantly influence the demand for and allocation of health promotion services.